The Effect of Leadership on Organizational Perfformance with the Burnout Phase as A Moderator in the IBM Student Union Organizations, Ciputra University - Amos, Angvedo Bryan; Effendy, Junko Alessandro; Soetandio, Linda Laurensia (Jurnal Entrepreneur dan Entrepreneurship, 2023)
One of the main factors in the success of an organization is leadership style. Leaders must always think about what style will be used to lead their organization so that organizational goals can be achieved with effective and efficient work patterns, and do not cause fatigue or what is commonly called burnout to every member who is a member of the organization. In this study, burnout acts as a moderator variable between leadership style and organizational performance. The purpose of this study was to determine the effect of leadership on organizational performance with burnout as a moderator at the IBM Student Union organization, Ciputra University. Respondents from this study were all 41 members of the IBMStudent Union of Ciputra University for the 2020/2021 period with the saturated sample method. The method used in this study uses the Partial Least Square (PLS) analysis method using SmartPLS software. The results of this study indicate that leadership affects organizational performance at the IBM Student Union for the 2020/2021 period and burnout does not moderate the relationship between leadership and organizational performance at the IBM Student Union for the 2020//2021 period.